Nuevos registros de Heteroptera (Hemiptera) acuáticos y semiacuáticos de Colombia (2016)
New records of sixteen species of water bugs are reported, belonging to 10 genera and seven families. Expansions of the geographical distribution are presented for 12 species and three species are recorded for the first time from Colombia: Ovatametra fusca Kenaga, 1942; Ovatametra gualeguay Bachmann, 1966 and Pseudosaldula saxicola Schuh and Polhemus, 2009, a diagnose and illustrations are included for each one of these species. Maps show the geographical distribution of all species.